EFEKTIVITAS MODEL PEMBELAJARAN SiMaYang BERBASIS ETNOSAINS JAMU KUNYIT ASAM PADA MATERI ASAM BASA UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA - Khoirunisa; Sunyono; Nuri Utami, Gamilla (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the effectiveness of SiMaYang-based ethoscience instruction on acids and bases in improving students’ science process skills. This study used two classes—an experimental class and a control class selected from three 11th-grade science classes at State High School 16 in Bandar Lampung for the 2025/2026 academic year, using cluster random sampling. This study employed a pretest-posttest control group design. The results showed that the average n-Gain for students’ science process skills in the experimental class was 0.71, meeting the “high” criterion, while in the control class it was 0.55, meeting the “moderate” criterion. The effect size test yielded a value of 0.98, classified as “large,” indicating that 98%. Based on the analysis, it can be concluded that the ethoscience-based SiMaYang learning model is effective in improving students’ science process skills in the acids and bases unit.